Biomass carbon quantum dot as well as preparation method and application thereof

Biomass carbon quantum dots prepared by flavonoid extraction and hydrothermal reaction of persimmon leaves solved the problem of the time spent on existing carbon quantum dots and the use of toxic substances, achieving efficient and environmentally friendly lead ion detection, and promoting carbon The application of quantum dots in practical applications.

CN119176549AInactive Publication Date: 2024-12-24HANDAN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411311151.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing carbon quantum dot preparation methods are too long and cumbersome to operate, and often use acidic or alkaline and toxic substances, which limits their application in heavy metal ion detection.

Method used

Using a preparation method of biomass carbon quantum dots, the flavonoid extraction of pulverized persimmon leaves and then hydrothermal reaction with distilled water at 190-210°C can be prepared to achieve excellent performance near-infrared fluorescent carbon quantum dots. It has a fast, simple, environmentally friendly preparation process and is used for lead ion detection.

Benefits of technology

High-sensitivity lead ion detection is achieved, simplifies operational steps, reduces costs, and promotes the application of carbon quantum dots in practical applications, avoiding the risk of using harmful chemicals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176549A_ABST
    Figure CN119176549A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of materials, and provides a biomass carbon quantum dot and a preparation method and application thereof.The preparation method comprises the steps that smashed persimmon leaves are subjected to flavone extraction treatment and dried, and a carbon source is obtained; the carbon source and distilled water are fully mixed and then placed at the temperature of 190-210 DEG C for a hydrothermal reaction for 4-6 h, after cooling and centrifugal treatment, obtained supernate is filtered and then dried, and the biomass carbon dot material is obtained; wherein the mass volume ratio of the carbon source to the distilled water is (0.25-0.35): 10. Persimmon leaf waste subjected to flavone extraction is used as a carbon source for the first time, the near-infrared fluorescent carbon quantum dots with excellent performance are prepared by adopting a simple one-step hydrothermal method, and the near-infrared fluorescent carbon quantum dots have the advantages of short time consumption, simple operation steps, relatively mild conditions, environmental friendliness, low cost and the like, can be successfully applied to detection of pollutant lead ions, and are high in detection sensitivity and good in application prospect. The practical application of the carbon quantum dots is greatly promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and in particular relates to a biomass carbon quantum dot and a preparation method and application thereof. Background Art

[0002] Carbon quantum dots generally refer to spherical carbon nanoparticles with a diameter of less than 10nm, or surface-modified nanoparticles. Due to their excellent physical and chemical properties, carbon dots are widely used in various fields such as cell imaging, drug carriers, photocatalysis and environmental testing. They are a new type of carbon nanomaterial that has attracted much attention internationally and are a hot topic in the field of carbon nanomaterials. At present, there is still room for exploration in the methods of preparing high-quality carbon dots, and the environmentally friendly method of preparing high-quality carbon dots is an issue that needs to be solved urgently.

[0003] The explosive growth of population and the rapid industrialization process have led to a sharp increase in the emission of heavy metal ions. These heavy metal ions are usually persistent and bioaccumulative in the environment. They are difficult to degrade in the environment and easily enter the human body through the food chain and respiratory tract, causing irreversible damage to human health. Therefore, it is urgent to develop a highly sensitive, highly selective, fast and convenient method for the detection of heavy metal lead ions. Biomass fluorescent carbon dots have received extensive attention in the detection of heavy metal ions due to their good biocompatibility, small size, easy labeling, strong photostability and low toxicity.

[0004] However, among the various carbon dot preparation methods currently available, many methods have defects such as being too time-consuming and cumbersome to operate, or most of the preparation processes require the use of some highly acidic or alkaline and toxic substances, which creates obstacles for the actual application of fluorescent carbon dots. Summary of the invention

[0005] The purpose of the embodiments of the present application is to provide a method for preparing biomass carbon quantum dots, aiming to solve the defects of existing carbon quantum dot preparation methods such as being too time-consuming and cumbersome to operate, as well as the problem of using highly acidic or alkaline and toxic substances in the preparation process.

[0006] The embodiment of the present application is implemented as follows: a method for preparing biomass carbon quantum dots, comprising:

[0007] The crushed persimmon leaves are subjected to flavonoid extraction treatment, and then dried to obtain a carbon source;

[0008] The carbon source and distilled water are mixed thoroughly and then subjected to hydrothermal reaction at 190-210° C. for 4-6 hours. After cooling and centrifugation, the obtained supernatant is filtered and dried to obtain a biomass carbon dot material.

[0009] Wherein, the mass volume ratio of the carbon source to distilled water is (0.25-0.35):10.

[0010] The embodiment of the present application also provides a biomass carbon quantum dot, which is prepared by the above-mentioned method for preparing the biomass carbon quantum dot.

[0011] The embodiments of the present application also provide an application of the above-mentioned biomass carbon quantum dots in lead ion detection.

[0012] The embodiment of the present application provides a method for preparing biomass carbon quantum dots. For the first time, persimmon leaf waste after flavonoid extraction is used as a carbon source, and a simple one-step hydrothermal method is adopted to prepare near-infrared fluorescent carbon quantum dots with excellent performance. The method has the advantages of short time consumption, simple operation steps, relatively mild conditions, environmental friendliness, and low cost. It has been successfully applied to the detection of pollutant lead ions with high detection sensitivity, which greatly promotes the application of carbon quantum dots in practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 A graph showing the relative quantum yield of carbon quantum dots obtained at different material-liquid ratios (a), reaction temperatures (b), and reaction temperatures (c) provided in the examples of the present application;

[0014] Figure 2 Response surface diagram of the effects of reaction time and liquid-to-solid ratio (a), reaction temperature and reaction time (b), reaction temperature and liquid-to-solid ratio (c) on relative quantum yield provided in the examples of the present application;

[0015] Figure 3 HRTEM image (a) and particle size analysis image (b) of biomass carbon quantum dots provided in the examples of the present application;

[0016] Figure 4 The X-ray powder diffraction pattern of the biomass carbon quantum dots provided in the examples of the present application;

[0017] Figure 5 Infrared spectra of biomass carbon quantum dots provided in the examples of this application;

[0018] Figure 6 The ultraviolet absorption spectrum of biomass carbon quantum dots provided in the examples of this application;

[0019] Figure 7 Fluorescence spectra of biomass carbon quantum dots provided in the examples and comparative examples of the present application;

[0020] Figure 8 Metal ion selective detection diagram provided for the test example of this application;

[0021] Fig. 9Fitted linear graph of the lead ion range provided for the test example of this application. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0023] Before 2010, most researchers only focused on the properties of carbon dots, and after 2010, the application of carbon dots was expanded. However, most researchers have overlooked the importance of carbon sources. Today, with energy becoming increasingly scarce, the use of biomass materials as carbon sources to prepare carbon dots has attracted the attention of more and more researchers. Compared with other carbon sources, biomass carbon sources are first of all eco-friendly natural additive-free, and have many advantages in preparing carbon dots, including low price, easy access, green environmental protection, and abundant resources. In addition, low-value waste can also be converted into high-value carbon dot materials. Therefore, it is very important to select a suitable carbon source and design and synthesize multifunctional composite materials. To realize the practical application of fluorescent carbon dots in many fields such as biology, environment, and energy, it is necessary to promote the large-scale production of high-quality fluorescent carbon dots at a lower cost. This application uses biomass waste persimmon leaves as raw materials to synthesize carbon dots for the first time. It is an ideal carbon dot synthesis approach that "turns waste into treasure", which is very consistent with the concept of "green chemistry".

[0024] The present invention provides a method for preparing biomass carbon quantum dots, comprising:

[0025] The crushed persimmon leaves are subjected to flavonoid extraction treatment, and then dried to obtain a carbon source;

[0026] The carbon source and distilled water are mixed thoroughly and then placed under a temperature condition of 190-210° C. for hydrothermal reaction for 4-6 hours. After cooling and centrifugation, the obtained supernatant is filtered and dried to obtain a biomass carbon dot material.

[0027] Wherein, the mass volume ratio of the carbon source to distilled water is (0.25-0.35):10.

[0028] In the embodiment of the present application, the method for extracting flavonoids from persimmon leaves can be implemented with reference to the prior art in the art, which can be: weigh a certain amount of persimmon leaf powder, perform ultrasonic extraction according to a certain feed liquid such as 1:20, ultrasonic temperature such as 40℃-70℃, ultrasonic time such as 15min-35min, ethanol concentration such as 40%-70%, filter, and put the filter residue into an oven to dry as a carbon source. The following specific embodiment is for the extraction of brass from persimmon leaves: weigh persimmon leaf powder, add 55% ethanol according to a feed liquid ratio of 1:20, set the ultrasonic temperature to 55℃, set the ultrasonic time to 20min for ultrasonic extraction, and put it into a 100℃ oven for drying for 10h-15h after filtering; although the embodiment is only exemplified by a single flavonoid extraction method, it should not be used to limit the scope of protection of this application. Those skilled in the art can refer to other prior art to extract flavonoids from persimmon leaves. It is worth noting that under the same conditions, the carbon quantum dots prepared from the carbon source after flavonoid extraction are superior to the carbon source without flavonoid extraction.

[0029] Preferably, the hydrothermal reaction temperature is 198-200°C.

[0030] Preferably, the hydrothermal reaction time is 5-5.5 hours.

[0031] Preferably, the mass volume ratio of the carbon source to distilled water is (0.25-0.3):10.

[0032] The following is a detailed description of the preparation method of biomass carbon quantum dots with specific examples, as shown below. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are all commercially available unless otherwise specified.

[0033] Example 1: Preparation of biomass carbon quantum dots

[0034] Fresh persimmon leaves are washed, dried, and crushed into tiny powders. After extracting persimmon leaf flavonoids, persimmon leaf waste is obtained as a carbon source for preparing carbon dots. Weigh 0.25-0.35g of persimmon leaf carbon source and 10mL of distilled water into a polytetrafluoroethylene-lined hydrothermal reactor, shake for 1 minute to fully mix the liquid, place it in a forced air drying oven at a temperature of 190-210°C, react fully for 4-6 hours under high temperature conditions, and cool naturally after the reaction is completed. The supernatant liquid is centrifuged and filtered to obtain a clear light yellow solution, which is dialyzed and vacuum freeze-dried to obtain carbon quantum dot powder.

[0035] Based on the experimental conditions of the above examples, single factor variation experiments with different mass volume ratios of carbon source to distilled water (material-liquid ratio), different reaction temperatures and different reaction times were designed. The corresponding relative quantum yield variation trends are shown in Figure 2. Figure 1 As shown. Figure 1It was found that the maximum emission peak of the fluorescence emission spectrum was located at 367nm, which belongs to the ultraviolet light region, so the carbon quantum dots emitted bright blue light under ultraviolet light. The half-peak width was 7nm, which was very narrow, indicating that the purity of the fluorescence was very high. The relative quantum yield reached its maximum value at the reaction time of 5h, the reaction temperature of 200℃, and the material-liquid ratio of 0.3g / 10mL.

[0036] On the basis of the above single factor experiment, the response surface experimental design was carried out using Design-Expert13 software. The experimental design and results are shown in Table 1, and the results of the regression model variance analysis are shown in Table 2.

[0037] Table 1 Box-Behnken experimental design and results

[0038]

[0039]

[0040] The multivariate regression equation is obtained by fitting:

[0041] Y=-352.45830+3.23035A+8.79900B+53.19300C-0.015000AB+0.255000AC+0.60000BC-0.007922A 2 -0.651200B 2 -181.2800C 2

[0042] Table 2.2 Analysis of variance of regression model

[0043]

[0044]

[0045] Note: **P<0.01 (extremely significant difference); *P<0.05 (significant difference); A: reaction temperature; B: reaction time; C: carbon source addition amount, R 2 =94.27%.

[0046] From Table 2, we know that the P value of the regression model is 0.0009 < 0.01, indicating that the model is very significant. The lack of fit term P = 0.1797 > 0.05 is not significant, indicating that the regression equation fits well. 2 , B 2 , C 2 The influence on relative quantum yield is extremely significant. However, the interaction terms AB, AC, and BC are not significant. The influence of the three factors on relative quantum yield is ranked as temperature > time > carbon source addition.

[0047] Further, by Figure 2 The strongest interaction was found between reaction temperature and carbon source addition. This interaction has the greatest impact on relative quantum yield, and its response surface is very steep, with obvious curvature and an elliptical contour. The interaction between reaction time and reaction temperature is weaker. The weakest interaction was found between reaction time and carbon source addition, with a contour line similar to a circle, a flat response surface and a small curvature. Comparison showed that this was consistent with the results of variance analysis.

[0048] According to the variance analysis of the experimental results and the regression equation, the optimal preparation conditions of persimmon leaf carbon quantum dots were optimized by response surface analysis: reaction temperature: 199.694℃; reaction time: 5.324h; carbon source addition: 0.269g. The relative quantum yield under these optimized conditions was 6.114%. The optimal process conditions obtained by response surface analysis were verified by experiment. In order to ensure the feasibility of the preparation process, the process conditions were fine-tuned to 200℃, 5.3h, and 0.27g of carbon source. The three groups of experiments were repeated and the relative quantum yield was 6.059%, which was very close to the predicted value. This shows that the quadratic regression equation is reliable and suitable for the analysis and prediction of the optimization process of persimmon leaf carbon quantum dots.

[0049] Example 2: Preparation of biomass carbon quantum dots

[0050] Fresh persimmon leaves were washed, dried, and crushed into tiny powders. After extracting persimmon leaf flavonoids, persimmon leaf waste was obtained as a carbon source for preparing carbon dots. 0.27 g of persimmon leaf carbon source and 10 mL of distilled water were weighed and placed in a polytetrafluoroethylene-lined hydrothermal reactor, shaken for 1 minute to fully mix the liquid, placed in a blast drying oven at 200 ° C, and fully reacted for 5.3 hours under high temperature conditions. After the reaction was completed, it was naturally cooled. The supernatant liquid was centrifuged and filtered to obtain a clear light yellow solution, which was dialyzed and vacuum freeze-dried to obtain biomass carbon quantum dot powder.

[0051] Comparative Example 1

[0052] Fresh persimmon leaves were washed, dried, and crushed into tiny powders as a carbon source for preparing carbon dots. 0.27 g of persimmon leaf carbon source and 10 mL of distilled water were weighed and placed in a polytetrafluoroethylene-lined hydrothermal reactor, shaken for 1 minute to fully mix the liquid, placed in a blast drying oven at 200 ° C, and fully reacted for 5.3 hours under high temperature conditions. After the reaction was completed, it was naturally cooled. The supernatant liquid was centrifuged and filtered to obtain a clear light yellow solution, which was dialyzed and vacuum freeze-dried to obtain biomass carbon quantum dot powder.

[0053] The biomass carbon quantum dot powder obtained in Example 2 was subjected to transmission electron microscopy (HRTEM) and particle size analysis. The results are as follows: Figure 3 As shown, the persimmon leaf carbon dots prepared in the present application are in the shape of an elliptical sphere, have good dispersibility, have obvious lattice fringes, and have an average particle size of 2.50 nm, which meets the size requirements of carbon dots.

[0054] Furthermore, the biomass carbon quantum dot powder obtained in Example 2 was characterized by X-ray powder diffraction (XRD). Figure 4 As shown, X-ray powder diffraction (XRD) measurement is used to confirm the graphitic nature of persimmon leaf carbon dots. It can be clearly seen that there are obvious diffraction peaks at 2θ=28.95° and 2θ=42°, corresponding to the graphite (002) diffraction crystal plane and the graphite (100) diffraction crystal plane, respectively. The diffraction peak intensity is very large, very narrow and sharp, indicating that the grains are large and the crystallinity is perfect, which is the characteristic diffraction peak of CDs.

[0055] Furthermore, the biomass carbon quantum dot powder obtained in Example 2 was subjected to infrared spectroscopy test. Figure 5 As shown, from Figure 5 It can be seen that there is a broad absorption peak at 3415.94 cm, which is attributed to the stretching vibration of OH and NH, the absorption peaks at 1617.23 cm and 1638.06 cm are attributed to the stretching vibration of C=O and C=C, respectively, the peak at 1400.71 cm is attributed to the stretching vibration of CN, and 1115.45 cm is the stretching vibration peak of unsaturated CO. This indicates that the surface of persimmon leaf carbon dots contains hydroxyl, amino and carboxyl groups, most of which are hydrophilic groups, making the carbon dots have excellent water solubility.

[0056] Furthermore, the biomass carbon quantum dot powder obtained in Example 2 was subjected to ultraviolet absorption spectrum test. Figure 6 As shown, it can be seen from the UV absorption spectrum that the carbon dot absorption peak is at 365nm, which is usually caused by n→π* transition;

[0057] Furthermore, the fluorescence spectra of the biomass carbon quantum dot powder obtained in Example 2 and Comparative Example 1 are as follows: Figure 7 As shown, under other same conditions, the carbon dots prepared from the carbon source after flavonoids extraction are superior to those prepared from the carbon source without flavonoids extraction.

[0058] Test Example 1: Carbon dot ion detection

[0059] Prepare 1×10 -3 mol / L of several common anions and cations, including various cations (Hg 2+ 、Ag + , Fe 3+ , Cu2+ 、Al 3+ 、Na + , Pb 2+ ) and various anions (Cl - 、NO3 - ). Take 0.1 mL of ion solution in 2.9 mL of water, then add 2 mL of carbon dot solution, and measure the maximum fluorescence emission intensity F at the maximum excitation wavelength of 310 nm. O -F) / F O The formula (F O The maximum fluorescence emission intensity is obtained when 2.9 mL of deionized water is added to 2 mL of carbon dot solution, and the fluorescence quenching diagram of the coexisting ions on the carbon dots is obtained.

[0060] In view of the excellent chemical and optical properties of persimmon leaf carbon dots, the fluorescence properties of 9 different metal ions were tested, with 334nm as the fluorescence excitation wavelength and the measurement range set to 340-500nm. Figure 8 As shown, from Figure 8 It can be seen that Pb 2+ The quenching of fluorescence performance by Pb ions is the most obvious. However, the quenching of fluorescence performance by other ions is weak or unchanged. 2+ ions, the fluorescence intensity of persimmon leaf carbon dots decreased significantly, and it can be used as a fluorescent probe to detect Pb 2 + ion.

[0061] Test Example 2: Pb 2+ Ion range detection

[0062] From the above selective detection, it can be seen that for Pb 2+ Ions are the most selective, and a certain amount of 0.1 mol / L Pb 2+ ions and diluted them to different concentrations, 10, 20, 30, 40, 50, 100umol / L, and performed fluorescence quenching detection, selecting 256nm as the excitation wavelength and the detection range of 265-400nm. Fig. 9 It can be seen that with the increase of Pb 2+ As the ion concentration increases, the fluorescence intensity of persimmon leaf carbon quantum dots decreases. Fig. 9 CQDs and Pb 2+ The quenching data of the ions were analyzed and the fluorescence intensity value and concentration were in a linear relationship Y = -0.7657X + 72.1549. The sum of squares of the residuals was 73.9886, R 2 =0.9849. This indicates that the fluorescence intensity is related to Pb 2+The linear relationship between ion concentrations was good, and the detection limit was 0.45 μmol / L. The prepared persimmon leaf carbon quantum dots can be used as a nanofluorescent probe to achieve quantitative detection of Pb 2+ ion.

[0063] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0064] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing biomass carbon quantum dots, characterized in that: include: The crushed persimmon leaves are subjected to flavonoid extraction treatment, and then dried to obtain a carbon source; The carbon source and distilled water are mixed thoroughly and then subjected to hydrothermal reaction at 190-210° C. for 4-6 hours. After cooling and centrifugation, the obtained supernatant is filtered and dried to obtain a biomass carbon dot material. Wherein, the mass volume ratio of the carbon source to distilled water is (0.25-0.35):

10.

2. The method for preparing biomass carbon quantum dots according to claim 1, characterized in that: The hydrothermal reaction temperature is 198-200°C.

3. The method for preparing biomass carbon quantum dots according to claim 1, characterized in that: The hydrothermal reaction time is 5-5.5 hours.

4. The method for preparing biomass carbon quantum dots according to claim 1, characterized in that: The mass volume ratio of carbon source to distilled water is (0.25-0.3):

10.

5. A biomass carbon quantum dot, characterized in that: The biomass carbon quantum dots are prepared by the method for preparing the biomass carbon quantum dots according to any one of claims 1 to 4.

6. Use of the biomass carbon quantum dots according to claim 5 in lead ion detection.